Synthesis of reduced graphene oxide/tungsten trioxide nanocomposite electrode for high electrochemical performance / Christelle Wong Pau Ping - Christelle Wong, Pau Ping (2017)
The consumption of non-renewable energy has raised severe environmental issues to the Earth. An increase in fossil fuel burning directly increased the volume of greenhouse gases. As results the Earth is getting warmer and sea levels increased continuously. In order to solve the problem, renewable energy resources have been intensively researched. However, renewable energy requires an energy storage device such as supercapacitor to maximize the utilization of energies. Electrode material is a promising target for the development of sustainable supercapacitor for future energy system. The formation of desired electrode material is essential in order to fabricate supercapacitor with higher power density and longer life cycle than secondary batteries in electronic application. In this study, Pre-oxidized reduced graphene oxide (P-rGO) was successfully synthesized through two-steps modified Hummers’ method followed by chemical reduction method. Based on the results, the synthesized P-rGO exhibited higher capacitance as compared to rGO that synthesized through single-step modified Hummers’ method. Continuous efforts have been exerted to further improve the electrochemical performance of P-rGO/WO3 nanocomposite by incorporating an optimum content of WO3 on P-rGO sheets using hydrothermal technique. In this manner, comprehensive investigations on different parameters, such as loadings of ammonium paratungstate (APT), hydrothermal temperature and reaction time were conducted in order to study the formation of P-rGO/WO3 nanocomposite. WO3 and P-rGO/WO3 nanocomposite were successfully synthesized through a simple hydrothermal method. It was found that P-rGO/WO3 nanocomposite in ratio of 1:100 and subsequently heat treated at 150 ºC for 20 hours demonstrated a maximum electrochemical behavior with specific capacitance of 274.0 F g-1 at a current density of 0.7 A g-1. This performance was approximately twice higher than the pure WO3. The presence of WO3 at 1:100 in P-rGO/WO3 nanocomposite showed an improvement in electrochemical performance because it acts as the spacer to prevent the restacking of P-rGO as well as to provide a larger surface area for electrolyte access. Moreover, the addition of P-rGO to nanocomposite could decrease the resistance of ions between the electrolyte and electrode, leading to fast electron transport.